in vitro ANGIOGENESIS CAPACITY OF MESENCHYMAL STEM CELLS DERIVED FROM UMBILICAL CORD BLOOD AND ADIPOSE TISSUE - Do Thi, Xuan Phuong; Thân, Thi Trang Uyên; Dinh, Duy Thanh; Hoang Thi, My Nhung; Do, Xuan Hai (Tạp chí Sinh lý học Việt Nam, 2022)
Objective: Angiogenesis plays an essential role in regenerative medicine and damaged tissue repair. Mesenchymal stem cells (MSCs) have been demonstrated to have angiogenic properties and therapeutic potential through their capacity to induce endothelial cell proliferation and tube formation. Besides, bone marrow-derived MSCs have been reported to form a tube-like structure on the Matrigel. In this study, we aimed to check the ability of adipose (AD) and umbilical cord blood (UCB) – derived MSCs in the tube formation and compare them to that of human umbilical cord vein endothelial cells (hUVECs). Methods: The Matrigel was used for the in vitro angiogenesis model. Results: We successfully isolated and cultured ADMSCs, UCBMSCs, and hUVECs with the high expression of specific cell type markers. Moreover, hUVECs could form a tube-like structure network and maintain this morphology for more than 8 hours. ADMSCs and UCBMSCs were able to form the tube-like structure at the early time of 2 hours but failed to retain the structure. Conclusion: ADMSCs and UCBMSCs had potential in the formation of tube-like structures in a short time.